Molecular variability of three genes of potato vein yellow virus infecting Solanum tuberosum, using single strand conformational polymorphism (2015)
Potato yellow vein virus (PYVV), a virus with tripartite RNA (ss+) genome is classified as member of the genus Crinivirus within the family Closteoviridae. PYVV is the causal agent of potato yellow vein disease (PYVD) with yield loss between 25 %–50 % in field. Single strand conformational polymorphism (SSCP) has been reported to estimate variability in different viruses’ species. In this study, the molecular variability of PYVV analyzed by SSCP patterns of three genes: major capsid protein (CP), minor capsid protein (CPm), and heat shock protein (Hsp70) obtained from 60 virus isolates from potato plants expressing PYVD. Leaves collected in Nariño, Colombia from 30 Solanum tuberosum Phureja Group (PhG) and 30 from the Andigena Group (AG). Genes amplified by RT-PCR and the purified PCR products used for SSCP. Three SSCP patterns detected for the CP gene, 12 for CPm and 12 for Hsp70. The pattern C was the most frequent for the Hsp70 gene and the pattern IV (33.3 %) for CPm gene in the Andigena Group. The pattern 1 for CP gene was present in 93.3 % of both host groups, indicating low number of variants compared to the CPm and Hsp70 genes. This is the first attempt to estimate intra e inter PYVV variability by the use of a simple molecular method considering three genes in a large group of potato samples affected by PYVD. SSCP technique was useful to evaluate the viral variability.